PERANCANGAN SISTEM INFORMASI PENJUALAN BERBASIS WEB PADA BURGER LUMER - Muhamad Irian Khairi Dzaky (2021)
purchasing information system made for Burger Lumer is a web-based application that is used to manage and control purchases in Burger Lumer. The system of purchasing information can make the purchase activity of assets owned by Burger Lumer. On the side of the display, this system uses an admin dashboard called bootflat-admin which is open source and remainsresponsive, of course, because it is made using the framework css bootsrap 3.2. This system is expected to help the performance in the management carried out by the store and safer and more transparent compared to the system that runs still uses paper. It is hoped that the purchase and sale of information systems for goods management will be more effective and efficient